2016
DOI: 10.1021/acsbiomaterials.6b00646
|View full text |Cite
|
Sign up to set email alerts
|

Crimped Nanofibrous Biomaterials Mimic Microstructure and Mechanics of Native Tissue and Alter Strain Transfer to Cells

Abstract: To fully recapitulate tissue microstructure and mechanics, fiber crimping must exist within biomaterials used for tendon/ligament engineering. Existing crimped nanofibrous scaffolds produced via electrospinning are dense materials that prevent cellular infiltration into the scaffold interior. In this study, we used a sacrificial fiber population to increase the scaffold porosity and evaluated the effect on fiber crimping. We found that increasing scaffold porosity increased fiber crimping and ensured that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 62 publications
(103 reference statements)
2
51
0
Order By: Relevance
“…Up to now, electrospun crimped ultrathin fibers have been produced from various polymers, including polyurethane (PU), polyacrylonitrile (PAN), polyamide‐6 (PA6), polycaprolactone (PCL), acrylic, polylactide (PLA), polyvinylidene fluoride (PVDF), poly (L‐lactide‐co‐ε‐caprolactone) (P(LLA‐CL)), poly (L‐lactide‐co‐acryloyl carbonate) (P(LLA‐AC)), poly(lactic‐ co ‐glycolic) acid (PLGA), poly‐L‐lactide (PLLA), and poly(ε‐caprolactone‐co‐acryloyl carbonate) (P(ε‐CL‐AC)), The polymer solutions of these polymers are summarized in Table .…”
Section: Generating Of Crimped Ultrathin Fibers By Electrospinningmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to now, electrospun crimped ultrathin fibers have been produced from various polymers, including polyurethane (PU), polyacrylonitrile (PAN), polyamide‐6 (PA6), polycaprolactone (PCL), acrylic, polylactide (PLA), polyvinylidene fluoride (PVDF), poly (L‐lactide‐co‐ε‐caprolactone) (P(LLA‐CL)), poly (L‐lactide‐co‐acryloyl carbonate) (P(LLA‐AC)), poly(lactic‐ co ‐glycolic) acid (PLGA), poly‐L‐lactide (PLLA), and poly(ε‐caprolactone‐co‐acryloyl carbonate) (P(ε‐CL‐AC)), The polymer solutions of these polymers are summarized in Table .…”
Section: Generating Of Crimped Ultrathin Fibers By Electrospinningmentioning
confidence: 99%
“…Szczesny et al fabricated crimped PLLA nanofibers using poly(ethylene oxide) (PEO) as the sacrificial fiber population. PEO was added to alter the mechanical properties of the PLLA fibers.…”
Section: Generating Of Crimped Ultrathin Fibers By Electrospinningmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that by changing the flow rate ratio between the core and sheath fluids, as well as PCL concentration (in the core fluid), we were able to achieve wavy and straight fibers with different sizes. These architectures have been previously fabricated using various techniques and in different size ranges; however, for our specific application of creating a 3D microenvironment to enhance neural progenitor cell differentiation into glial cells, using fibers in similar size range of cells is preferred . After culturing the AHPCs on the microfibrous scaffolds of various diameters and topographies, we found that the larger diameter microfibers appear to guide the differentiation to mature neurons, whereas all PCL microfibers promoted astrocyte differentiation.…”
Section: Introductionmentioning
confidence: 98%